PSEUDO ALGEBRAS BOOL APPLIED BL-ALGEBRAS - Olimpia-Mioara PECINGINA; Constantin BOGDAN (Fiabilitate şi Durabilitate)
In this article we study Boolean algebras in terms of Hilbert algebras and deductive systems